Aging Behind Bars: Challenges of Healthcare for Elderly Prisoners - Kraljić, Suzana (65 pravne znanosti v Mariboru, 2026)
Modern criminal justice systems are increasingly faced with the challenge of an aging prison population, with elderly prisoners representing one of the most vulnerable groups within correctional institutions. These individuals often experience accelerated physical and mental aging, further exacerbated by restrictive living conditions and insufficient access to adequate healthcare. While international and national law (e.g., the prohibition of torture and inhuman or degrading treatment) mandates respect for human dignity, a range of legal and ethical challenges continue to arise in everyday life regarding the healthcare of prisoners. These include issues related to compassionate release, the care of terminally ill prisoners, and the treatment of prisoners with mental health problems. This chapter analyzes the Slovenian legal framework and dilemmas that are encountered in providing healthcare to elderly prisoners, who represent one of the marginalised population groups. The challenges of healthcare provision for elderly prisoners are also examined in the context of the case law of the European Court of Human Rights.